2004
DOI: 10.1002/app.21219
|View full text |Cite
|
Sign up to set email alerts
|

Surface photografting polymerization of vinyl acetate, maleic anhydride, and their charge‐transfer complex. V. Charge‐transfer complex (1)

Abstract: ABSTRACT:In previous studies, the photografting polymerization of vinyl acetate (VAC) and maleic anhydride (MAH) was investigated systematically. After that, to increase the grafting rate and efficiency and make the project more practicable, a VAC-MAH binary monomer system was employed for simultaneous photografting onto the surface of low-density polyethylene film. The effects of several crucial factors, including the composition and total concentration of the monomer solution and different types of photoinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Instead, a broadening of the PLA CO band was observed, which would be the case if the amount of MAH grafted onto the PLA were low. It has previously been shown that MAH is difficult to homopolymerize and it is most often found in copolymers. MAH will thus form something similar to a monolayer on the substrate which would be difficult or impossible to observe with FTIR, since the depth of analysis of FTIR is approximately 1 μm. This means that a quite thick graft layer is required to prevent measurement of the bulk material as well.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, a broadening of the PLA CO band was observed, which would be the case if the amount of MAH grafted onto the PLA were low. It has previously been shown that MAH is difficult to homopolymerize and it is most often found in copolymers. MAH will thus form something similar to a monolayer on the substrate which would be difficult or impossible to observe with FTIR, since the depth of analysis of FTIR is approximately 1 μm. This means that a quite thick graft layer is required to prevent measurement of the bulk material as well.…”
Section: Resultsmentioning
confidence: 99%